2016
DOI: 10.1111/1742-6723.12683
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods used to quantify general practice‐type patients in the emergency department: A tertiary paediatric perspective

Abstract: We demonstrated that current models to quantify perceived GP-type presentations were inconsistent in paediatric patients. All methods flagged a high proportion of GP-type presentations, and although the reasons for these presentations are multifactorial and not easily explained by access to GP services alone, they do represent a significant workload in the paediatric ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 25 publications
(79 reference statements)
4
29
0
Order By: Relevance
“…For ED patients expected to be discharged home, four out of five seen were determined by the GPs to be manageable in general practice, with about one‐third of these requiring additional skills or resources. The identified percentage of PCTED presentations was higher in outer metropolitan and rural hospitals than tertiary metropolitan hospitals, as has been seen previously . There was very good agreement between the GPs and treating ED physicians although this decreased with higher urgency ATS category.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…For ED patients expected to be discharged home, four out of five seen were determined by the GPs to be manageable in general practice, with about one‐third of these requiring additional skills or resources. The identified percentage of PCTED presentations was higher in outer metropolitan and rural hospitals than tertiary metropolitan hospitals, as has been seen previously . There was very good agreement between the GPs and treating ED physicians although this decreased with higher urgency ATS category.…”
Section: Discussionsupporting
confidence: 77%
“…Agreement between previous indirect criteria used to identify PCTED presentations and assessment by GPs was then examined. Table shows the percentage of ‘seen’ and ‘present’ patients who were GP‐referred, arrived by ambulance, or had a diagnosis on the list previously identified in the literature . The percentage of ‘seen’ patients who were GP‐referred (13%) was similar to those ‘present’ in the EDs (12%), and, of these, 45 (80%) were classified as PCTED presentations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, due to the use of many other diagnosis codes for children with fever, such us respiratory tract infections, this study would underestimate the full impact of childhood fever on the ED. Lastly, while the AIHW method used to classify potentially avoidable, GP‐type was dependent on the variables available in our dataset, it has been suggested that other methods may be more suitable to estimate the proportion of GP‐type patient attendees . It is important to note that there is considerable variation in the proportion of GP‐type presentations identified in the paediatric population, depending on the method used .…”
Section: Discussionmentioning
confidence: 90%